Workplace approaches to teaching digital accessibility: establishing a common foundation of awareness and understanding - Lewthwaite, Sarah; Horton, Sarah; Coverdale, Andy (Frontiers in Computer Science, 2023)
Accessibility in the digital world is a shared responsibility, requiring a common foundation of awareness and understanding. However, little is known about how digital accessibility can be effectively taught, and research on workplace teaching and training in accessibility is highly scarce, despite its crucial role in building accessibility capacity in the workforce. This paper considers workplace accessibility pedagogy to focus on aspects of foundational education, characterised as a pedagogically informed set of teaching strategies, cultivated through organisational and workplace cultures and practices. It contributes an analysis and synthesis of pedagogic research with 55 experienced accessibility educators in higher education and the workplace, in the UK and internationally, drawing on insights from expert panel methods including interviews, forums and focus groups. We find that digital accessibility is identified as a necessary core competency for an inclusive digital world. We examine the prevalent approaches that experienced workplace educators use to establish foundational awareness and understanding of accessibility to enable learners to achieve core learning objectives. We report the challenges that workplace educators face, negotiating different contexts and working practices and adapting foundational learning experiences to meet the pedagogic demands of different roles, responsibilities and specialist advancement. In doing so, we demonstrate that establishing a common foundation of awareness and understanding is the basis for a pedagogic framework for digital accessibility education, with relevance for both workplace and academic settings.